2003
DOI: 10.1055/s-2003-37254
|View full text |Cite
|
Sign up to set email alerts
|

Argon Plasma Coagulation after Piecemeal Polypectomy of Sessile Colorectal Adenomas: Long-Term Follow-Up Study

Abstract: APC used in combination with piecemeal polypectomy of large colorectal adenomas is an effective and safe method of therapy, provided patient selection is careful and follow-up close.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
68
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 8 publications
7
68
1
6
Order By: Relevance
“…Zlatani et al (22) found a recurrence rate of some 50% in 47 patients with piecemeal resection alone, and similar recurrence rate in 30 patients initially treated by piecemeal resection followed by APC. regula et al (2), in a group of 63 patients, obtained complete initial eradication after piecemeal resection and APC in 90%, and a recurrence rate of 14% at follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…Zlatani et al (22) found a recurrence rate of some 50% in 47 patients with piecemeal resection alone, and similar recurrence rate in 30 patients initially treated by piecemeal resection followed by APC. regula et al (2), in a group of 63 patients, obtained complete initial eradication after piecemeal resection and APC in 90%, and a recurrence rate of 14% at follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…39,40 However, a recent study from Poland revealed that argon plasma coagulation did not reduce the recurrence rate compared to polypectomy alone. 41 Besides, a study from Italy reported that EMR was performed for 139 SP in 136 patients by snare polypectomy, and invasive carcinoma was found in 17 cases. 42 After 12 months of follow up after EMR, no local recurrence was detected in 7 patients with invasive carcinoma without surgery.…”
Section: Colorectummentioning
confidence: 99%
“…С 1991 г. в «гибкой» эндоскопии получил распространение метод АПК, обладающий 2 важными качествами: с одной стороны, обеспечивает эффектив-ную коагуляцию обширных поверхностей, с другой -позволяет выполнять коагуляцию при хорошо регули-руемой и равномерной глубине проникновения [26]. АПК применяют для снижения частоты рецидива при фрагментарном удалении диатермической петлей аденом прямой и ободочной кишки [27][28][29][30][31][32]. В насто-ящем исследовании мы стремились дать свою оценку данному методу при удалении LST-G с низким риском подслизистой инвазии, локализованных в прямой кишке.…”
unclassified